Synergistic Effect of Allium-like Ni9S8 & Cu7S4 Electrodeposited on Nickel Foam for Enhanced Water Splitting Activity - Mottakin M.; Selvanathan V.; Ariful Islam M.; Almohamadi H.; Alharthi N.H.; Yoshimura S.; Akhtaruzzaman M. (John Wiley and Sons Ltd, 2025)
This study explores a water-splitting activity using a biphasic electrodeposited electrode on nickel foam (NF). The *Ni9S8/Cu7S4/NF electrode with citric acid reduction exhibits superior OER (oxygen evolution reaction) and HER (hydrogen evolution reaction) performance with reduced overpotential and a steeper Tafel slope. The *Ni9S8/Cu7S4/NF electrode displays the ultra-low overpotential value of 212 mV for OER and 109 mV for HER at the current density of 10 mA cm?2. The Tafel slope of 25.4 mV dec?1 for OER and 108 mV dec?1 for HER was found from that electrode. The maximum electrochemical surface area (ECSA), lowest series resistance and lowest charge transfer resistance are found in citric acid reduced electrode, showing increased electrical conductivity and quick charge transfer kinetics. Remarkably, the *Ni9S8/Cu7S4/NF electrode demonstrated excellent stability for 80 hours in pure water splitting and 20 hours in seawater splitting. The synergistic effect of using bimetallic (Cu&Ni) sulfide and enhanced electrical conductivity of the electrode are caused by reduction of metal sulfide into metallic species resulting in improved water splitting performance. ? 2023 Wiley-VCH GmbH.